IMPLEMENTASI KEBIJAKAN PENDIDIKAN ONLINE SELAMA MASA PANDEMI COVID-19 - Deding Ishak (Jurnal Kelola: Jurnal Ilmu Sosial, 2020)
In 2019, the emergence of the Covid-19 virus in China caused a lot of anxiety. Then in 2020, this virus continued to spread throughout the world, resulting in a pandemic. The existence of this pandemic has changed many aspects of life, including aspects of teaching and learning activities in schools. Indonesia as a country that was also affected by the effects of this pandemic then tried to implement distance learning activities. Unfortunately, the implementation of this education policy is still not perfect, causing many students to find it difficult because this policy has not been carried out optimally. This study uses the results of previous studies and existing reports on the effects of the pandemic on education in the areas of Indonesia that experienced the most severe effects as a result of the pandemic. The results of this study then show that virtually, the infrastructure for conducting online learning has been formed, but unfortunately there are still various factors that hinder the implementation of online education policies, such as looser regulations for students in the online school learning process, teaching staff who still do not understand technology and parents who do not understand the distance learning process.